PERAN GURU PENDIDIKAN AGAMA ISLAM (PAI) DALAM UPAYA PEMBENTUKAN KARAKTER DISIPLIN SISWA DI SDIT DAARUL HASANAH JAKARTA SELATAN - Litakuna Karima; Munawaroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The importance of the role of Islamic religious education teachers in improving student discipline, supporting and inhibiting factors that shape students' disciplined character, efforts made by Islamic religious education teachers in shaping students' disciplined character. There needs to be habits so that students' disciplined character is formed. So that it is related to the problem that the author wants to research. Therefore, the purpose of this study is to determine the role of Islamic Religious Education teachers in efforts to shape the disciplined character of students at SDIT Daarul Hasanah. The method used in this study is a qualitative method with a descriptive approach. The number of informants consists of the principal, 1 Islamic Religious Education teacher, 6 students. data collection techniques include observation, interviews and documentation. while data analysis techniques are used to collect data, data reduction and conclusions. The results of the study show that student discipline at SDIT Daarul Hasanah has been running well. the supporting factors are good coordination between Islamic Religious Education teachers and the part in implementing SOP or school regulations. where students who violate the rules are punished so that what was initially bad becomes better.